2011
DOI: 10.1166/jnn.2011.4328
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Single-Electron Transistors Using Field-Emission-Induced Electromigration

Abstract: A novel technique for the integration of planar-type single-electron transistors (SETs) composed of nanogaps is presented. This technique is based on the electromigration procedure, which is caused by a field emission current. The technique is called "activation." By applying the activation to the nanogaps, SETs can be easily obtained. Furthermore, the charging energy of the SETs can be controlled by adjusting the magnitude of the applied current during the activation process. The integration of two SETs was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…14 We have also demonstrated a method for the integration of two SETs with similar electrical properties using the activation procedure, and the charging energies of the two SETs can be controlled simultaneously by the preset current used in the activation procedure. 15,16 Consequently, it is believed that the electrical properties of nanogap-based tunneling devices can be tuned by adjusting the magnitude of the preset current during the activation procedure.…”
Section: Introductionmentioning
confidence: 99%
“…14 We have also demonstrated a method for the integration of two SETs with similar electrical properties using the activation procedure, and the charging energies of the two SETs can be controlled simultaneously by the preset current used in the activation procedure. 15,16 Consequently, it is believed that the electrical properties of nanogap-based tunneling devices can be tuned by adjusting the magnitude of the preset current during the activation procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The activation method is based on moving the atoms induced by the Fowler-Nordheim (F-N) field emission current passing through the nanogaps between source and drain electrodes [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In the activation procedures, it is expected that the moved atoms accumulate within the gaps and play the dual role of reducing the gap width and forming SETs islands [15][16][17][18]. In fact, we were easily able to fabricate the SETs operating at room temperature [15,18].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, we were easily able to fabricate the SETs operating at room temperature [15,18]. Furthermore, the charging energy of the SETs and the number of islands were precisely controlled and adjusted by both the field emission current through a nanogap and the initial gap separation of the nanogaps [15][16][17][18]. Therefore, by precisely tuning the activation parameters, it is suggested that we can easily and simply fabricate the SETs with single and multiple islands.…”
Section: Introductionmentioning
confidence: 99%
“…The activation method is based on moving the atoms induced by the Fowler-Nordheim (F-N) field emission current passing through the nanogaps between source and drain electrodes [6][7][8][9][10][11][12][13]. In the activation procedures, it is expected that the moved atoms accumulate within the gaps and play the dual role of reducing the gap width and forming the SETs islands [12,13]. In fact, we were easily able to fabricate the SETs operating at room temperature [12].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, we were easily able to fabricate the SETs operating at room temperature [12]. Furthermore, the charging energy of the SETs and the number of islands were precisely controlled and adjusted by the field emission current passing through the nanogap [12,13]. Therefore, by precisely tuning the activation parameters, it is considered that we can easily and simply fabricate the SETs with single and multiple islands.…”
Section: Introductionmentioning
confidence: 99%